Analisis Learning Obstacle Siswa pada Materi Peluang Berbasis Literasi Matematis dengan Pendekatan Didactical Design Research - Rachmawati Khaerun Nisa; Lukman Lukman; Sufyani Prabawanto (Universitas Muhammadiyah Surabaya, 2025)
Mathematical literacy is a fundamental competency for the twenty-first century; however, students continue to experience significant learning obstacles in probability. This study aims to conduct an in-depth analysis of the learning obstacles encountered by eleventh-grade senior high school students in probability within the context of PISA-based mathematical literacy using the Didactical Design Research (DDR) approach. The study was conducted at a senior high school in Kuningan Regency, West Java, Indonesia, involving 36 students who participated in the diagnostic test stage. Using purposive sampling based on the variation of learning obstacle typologies (ontogenic, didactical, and epistemological), 10 students were selected for in-depth interviews. The data were analyzed qualitatively through data triangulation, including data reduction, data display, and conclusion drawing. The findings revealed that, at the formulate stage, students experienced epistemological and ontogenic obstacles characterized by difficulties in abstracting verbal situations into formal mathematical models and by mathematical anxiety. At the employ stage, substantial epistemological obstacles emerged due to inadequate prerequisite knowledge of set theory, procedural errors in fraction operations, and excessive reliance on memorizing formulas. Meanwhile, at the interpret stage, students were unable to relate numerical results back to their real-world contextual meanings. The novelty of this study lies in its simultaneous mapping of learning obstacles across the three PISA mathematical literacy processes—formulate, employ, and interpret—which served as the foundation for designing Didactical Pedagogical Anticipation (DPA) and reconstructing the recommended Hypothetical Learning Trajectory (HLT) from three to six instructional sessions.